Application for breast cancer classification using Computational Intelligence techniques - Oliveira, Manoel; Muniz, Felipe; Farrapo, Ruann (Anais da Escola Regional de Computação do Ceará, Maranhão e Piauí (ERCEMAPI); 2020: Anais da VIII Escola Regional de Computação do Ceará, Maranhão e PiauíDO - 10.5753/ercemapi.2020.11473, 2020)
In this work, a comparative study was carried out between two classification methods: The Multi layer Perceptron Artificial Neural Network (MLP ANN) and the method of classification of the Nearest Neighbors, used in the classification of the diagnosis of breast cancer. The data used in this work were taken from the UCI Machine Learning Repository and contains numerical data extracted from mammography images.In addition, the results were evaluated based on the cross-validation strategy.